Evaluating the utility of the Talent Development Environment Questionnaire as a tool to drive excellence in elite sport environments - Halland, A. J. A.; Jones, L.; Martindale, R. J. J. (2019)
Currently, little work has evaluated the impact of interventions within talent development environments(TDEs). This study is the first of its kind to evaluate the efficacy of utilising the Talent Development Environment Questionnaire (TDEQ) as a tool to help coaches and support staff gain feedback, structure interventions,and evaluate impactover a 12-month period of an international elite TDE. Sixteen full time professional male rugby union players, the Chief Rugby Operations Officer, General Manager of Rugby Performance, and the Head of the Elite RugbyProgram participated in the research. The TDEQ baseline results identified 17 weaknesses and nine strengths. Subsequently, an evidence based intervention designed by a staff and player working group was implemented. After the 12-month intervention, there were five weaknesses and 18 strengths with seven targeted and five non-targeted TDEQ items showed statistically significant improvements. Implications for practioners and policy makers on the use of the TDEQ as a mechanism for evidence based impact on evaluation, intervention design,and monitoring in elite TDEs are discussed